Feeling Useless: The Effect of Unemployment on Mental Health in the Great Recession - Lídia Farré; Francesco Fasani; Hannes Mueller (Institute for the Study of Labor (IZA), 2015)
This article documents a strong connection between unemployment and mental disorders using data from the Spanish Health Survey. We exploit the collapse of the construction sector to identify the causal effect of job loss. Our results suggest that an increase of the unemployment rate by 10 percent due to collapse of the sector raised mental disorders in the affected population by 3 percent. We argue that the large size of this effect responds to the fact that the construction sector was at the centre of the macroeconomic shock. As a result, workers exposed to the negative employment shock faced very low chances of re-entering employment. We show that this led to long unemployment spells, hopelessness and feelings of uselessness.
Keywords: I10; J60; C26; 330; mental health; great recession; unemployment; Spain